1984
DOI: 10.1055/s-0038-1661163
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Anticoagulant Effect of Hirudin in Man

Abstract: SummaryThe pharmacokinetics and the effects on the haemostatic system of hirudin were assessed in six healthy subjects after single intravenous or subcutaneous dose (1000 AT-U/kg). When hirudin was given intravenously first-order elimination kinetics followed the initial distribution phase. The decline in plasma hirudin concentration was most adequately expressed by a biexponential equation describing a two compartment model. A mean elimination half-life of 0.84 hr and a mean volume of distribution of 12.9 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
73
1
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(78 citation statements)
references
References 9 publications
3
73
1
1
Order By: Relevance
“…PAR-1 activation can be blocked by hirudin, a highly specific noncovalent thrombin inhibitor produced by the salivary glands of the leech Hirudo medicinalis (23). One of the limiting factors for its therapeutic use is its rapid elimination from the circulation with a plasmatic half-life of about 1 hour (24). Polyethyleneglycolhirudin (PEG-hirudin), a recombinant hirudin covalently bound to two PEG-5,000 residues exhibits a significantly prolonged half-life (8-9 hour) with no loss of potency or specificity (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…PAR-1 activation can be blocked by hirudin, a highly specific noncovalent thrombin inhibitor produced by the salivary glands of the leech Hirudo medicinalis (23). One of the limiting factors for its therapeutic use is its rapid elimination from the circulation with a plasmatic half-life of about 1 hour (24). Polyethyleneglycolhirudin (PEG-hirudin), a recombinant hirudin covalently bound to two PEG-5,000 residues exhibits a significantly prolonged half-life (8-9 hour) with no loss of potency or specificity (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental phar macological studies have shown that it is a highly active anticoagulant [1][2][3][4]. Recombi nant technology has made hirudins avail able.…”
Section: Introductionmentioning
confidence: 99%
“…Hirudin acts differently, directly and highly specifically to bind thrombin without inhibition of other proteases.10-14 Because hirudin reacts stoichiometrically in a 1:1 ratio with thrombin with a very low dissociation constant, the amount of drug needed to prevent thrombosis should be an indirect measure of the amount of thrombin generated. [10][11][12] The aims of the current study, in a deep arterial injury model, were to test whether 1) a conventional dosage of heparin will reduce platelet deposition and the incidence of mural thrombosis compared with placebo, 2) hirudin will produce a dose-dependent reduction in quantitative platelet and fibrinogen deposition and the incidence of mural thrombosis; the lowest effective activated partial thromboplastin time (APTT) prolongation for the prevention of arterial thrombosis can be established, 3) the APTT during hirudin therapy will correlate inversely with the platelet and fibrinogen deposition, and the incidence of mural thrombosis; the APTT and the thrombin time will provide a direct measure of hirudin blood levels; and 4) doses of heparin and hirudin sufficient to inhibit platelet aggregation to thrombin and prolong the bleeding time will reduce platelet deposition and mural thrombosis compared with placebo. were randomly allocated to one of five treatment groups: placebo (0.9% saline), sodium heparin at 50 units/kg (from porcine intestine that contained 1,000 USP units/ml) or recombinant desulfato hirudin (CGP 39393; sequence of hirudin variant 1 but lacks sulfate on tyrosine 63; specific activity, 11,496 ATU/ mg; known as hirudin in the text) at 0.3, 0.7, or 1.0 mg/kg.…”
mentioning
confidence: 99%